Door-to-door transportation of finished vehicles - Åberg, Ellen; Thinning, Joakim; Johansson, Martin (My University, 2012)
Door-to-door services are used by automobile manufacturers for transportation of finished vehicles from production plant to dealers. These services are provided by themselves or through third- and fourth part logistical companies, which have different assets and backgrounds. The aim of this study is to give an insight to this market and the companies active by presenting their services and resources and to identify the advantages and disadvantages between different types of asset management. The objective is also to identify the current status on the market and the influential force behind the development. The methodology of the study was based on qualitative methods of data collection. Primary data was provided through semi-structured interviews, conducted both written and verbal and supporting data was collected from literature, articles and webpages. The participating companies were selected because they offered a service that included the different elements identified in a door-to-door service. Of the four companies, two were third party logistics providers, while the other two were fourth party logistics providers. The framework of Porter’s Five Forces was chosen to analyse the result to identify the external forces that affect a company and the competitive strengths and weaknesses. In the interviews the companies described their work and their cooperation with their suppliers and customers and also their view on the future and the existing competition. The thesis presents a market where the customer has a lot of power and the suppliers need to adapt to them. The manufacturers wish to maintain control over the outbound supply chain and some have their own logistics companies to gain advantages from economy of scale. Furthermore two of the companies indicated that Europe is a stressed market with relativity small potential growth.
Keywords: Maskinteknik; Farkostteknik; Transport; Mechanical Engineering; Vehicle Engineering; Transport